NUTRIENT ENRICHMENT POTENTIAL OF FLOATING AQUATIC MACROPHYTE, EICHHORNIA CRASSIPES - AFTABUDDIN, MD.; HASSAN, M. A. (Journal of the Inland Fisheries Society of India, 2021)
The impact of different growth stages of water hyacinth on its decomposition loss of biochemical nutrients and enrichment of essential nutrients in ambient water was assessed. Maximum loss of biomass (59.91 ± 1.5 %), organic matter (60.1 ± 1.07%) and crude protein (70.72 ± 1.06 %) and lowest loss of mineral matter (57.02 ± 0.2%) was observed in decomposing brown leaf litter. Among green leaf litter, senescent stage showed significantly lower loss of mass (35.17 ± 2.74%), organic matter (31.23 ± 1.62 %) and crude protein (47.11 ± 1.65%) as compared to young ones. The sequence of loss of biochemical components for all leaf litter was crude protein > ash > organic matter. pH increased by 0.3 unit in both young green and senescent green plant with no changes in brown decomposing stage. Higher enrichment of ambient water in term of specific conductivity, available nitrogen and dissolved organic matter for both types of green than decomposing brown litter to a tune of 3.2-3.37, 4.3 and 4.26-4.87 fold as of initial value, respectively. Soluble reactive phosphorus enrichment was highest in decomposing brown litter followed by senescent green with no change for young green stage. Key words: Decomposition, nutrient enrichment, biochemical composition, Eichhornia crassipes, water hyacinth